2021
DOI: 10.1101/2021.03.09.434592
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Potent neutralizing nanobodies resist convergent circulating variants of SARS-CoV-2 by targeting novel and conserved epitopes

Abstract: There is an urgent need to develop effective interventions resistant to the evolving variants of SARS-CoV-2. Nanobodies (Nbs) are stable and cost-effective agents that can be delivered by novel aerosolization route to treat SARS-CoV-2 infections efficiently. However, it remains unknown if they possess broadly neutralizing activities against the prevalent circulating strains. We found that potent neutralizing Nbs are highly resistant to the convergent variants of concern that evade a large panel of neutralizing… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 51 publications
1
26
0
Order By: Relevance
“…Consistent with the results of mutational scanning, the engineered charge reversal on R31 (R31D) is unable to recover the salt bridge and restore binding to the E484K mutant. 45, 46…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with the results of mutational scanning, the engineered charge reversal on R31 (R31D) is unable to recover the salt bridge and restore binding to the E484K mutant. 45, 46…”
Section: Resultsmentioning
confidence: 99%
“…46 The reported cryo-EM structures for different classes of nanobodies suggested mechanisms of high-affinity and broadly neutralizing activity by exploiting epitopes that are shared with antibodies as well as novel epitopes that are unique to the nanobodies. 46 Another diverse repertoire of high affinity nanobodies against SARS-CoV-2 S protein that are refractory to common escape mutants and showed synergistic neutralizing activity are characterized by proximal but non-overlapping epitopes suggesting that multimeric nanobody combinations can improve potency while minimizing susceptibility to escape mutations. 47 These studies identified a group of common resistant mutations in the dynamic RBM region (F490S, E484K, Q493K, F490L, F486S, F486L, and Y508H) that evade many individual nanobodies.…”
Section: Introductionmentioning
confidence: 99%
“…Nanobodies are single domain antibodies that are generated from immunized llamas, camels and phage displays [85][86][87][88]. Recent published evidence shows that multivalent nanobodies are capable of both neutralizing circulating variants and preventing emergence of resistant escape mutants via binding to multiple, non-overlapping epitopes, avidity effects and binding to conserved epitopes largely inaccessible to normal antibodies [89][90][91][92][93][94][95][96]. Table 1 summarizes the main findings from these studies.…”
Section: Neutralizing Antibodiesmentioning
confidence: 99%
“…25 Nonetheless, many potentially neutralizing nanobodies also recognize regions of RBD that are subject to escape variation, reducing their potential efficacy. 26-28 Potent neutralizing nanobodies that resist convergent circulating variants of SARS-CoV-2 by targeting novel and conserved epitopes were recently reported. 26 Cryo-EM structure determination of different classes of nanobodies revealed mechanisms of high-affinity and broadly neutralizing activity against the evolving virus by exploiting novel epitopes on the SARS-CoV-2 S protein that are not accessible to antibodies.…”
Section: Introductionmentioning
confidence: 99%
“…26 Cryo-EM structure determination of different classes of nanobodies revealed mechanisms of high-affinity and broadly neutralizing activity against the evolving virus by exploiting novel epitopes on the SARS-CoV-2 S protein that are not accessible to antibodies. 26…”
Section: Introductionmentioning
confidence: 99%